1999
DOI: 10.1161/01.hyp.34.2.229
|View full text |Cite
|
Sign up to set email alerts
|

Apoptosis During Regression of Cardiac Hypertrophy in Spontaneously Hypertensive Rats

Abstract: Abstract-We previously reported that increased apoptosis participates in the regression of aortic hypertrophy in spontaneously hypertensive rats. To further document the potential role of apoptosis in cardiovascular therapy, we examined apoptosis during regression of hypertrophy in the heart of spontaneously hypertensive rats receiving the antihypertensive drug enalapril (30 mg ⅐ kg) for 1 to 4 weeks, starting at 10 to 11 weeks of age. Systolic blood pressure and heart rate were measured by the tail-cuff metho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
43
0

Year Published

2000
2000
2009
2009

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 67 publications
(46 citation statements)
references
References 51 publications
3
43
0
Order By: Relevance
“…Nifedipine was shown to block calcium-mediated apoptosis in isolated chick cardiomyocytes. 24 In contrast, Tea et al 25 reported that cardiac apoptosis transiently increased in SHR chronically treated with nifedipine but returned to baseline values at the end of the treatment period. Thus, our data in amlodipine-treated hypertensives would suggest that dihydropyridines do not exert long-term effects on cardiac apoptosis in hypertension.…”
Section: Discussionmentioning
confidence: 92%
“…Nifedipine was shown to block calcium-mediated apoptosis in isolated chick cardiomyocytes. 24 In contrast, Tea et al 25 reported that cardiac apoptosis transiently increased in SHR chronically treated with nifedipine but returned to baseline values at the end of the treatment period. Thus, our data in amlodipine-treated hypertensives would suggest that dihydropyridines do not exert long-term effects on cardiac apoptosis in hypertension.…”
Section: Discussionmentioning
confidence: 92%
“…These include an ACE inhibitor (enalapril), an angiotensin II receptor blocker (losartan), and a diuretic (furosemide) that have all been shown to be very effective in preventing or reversing LVH in animals including mice (37,(51)(52)(53)(54)(55)(56)(57)(58). Thus, in Npr1 -/-mice BP independent stimuli contribute to the development of LVH.…”
Section: Discussionmentioning
confidence: 99%
“…17,21,22 Other groups 18,20 have confirmed these effects in adult SHR and failing aged SHR. In the same experimental model, Tea et al 47 recently analyzed the effects that a 4-week administration of different antihypertensive drugs had on cardiac hypertrophy regression and on the DNA fragmentation index. Basically, they showed that renin-angiotensin system intervention and ␤-adrenergic blockade produced an increment of apoptosis in parallel to cardiac hypertrophy regression; calcium channel antagonists produced a time window of apoptosis after the first week of administration, whereas hydralazine and hydrochlorothiazide did not modify either cardiac hypertrophy or DNA fragmentation.…”
Section: Effects Of Antihypertensive Drugsmentioning
confidence: 99%